Action Research Remuneration System Development at RS Siti Khodijah Muhammadiyah Branch Sepanjang - widiastuti widiastuti; Nur Hidayah (Program Studi Magister Manajemen Rumah Sakit, Jenjang Pasca Sarjana (S2), Pasca Sarjana Universitas Muhammadiyah Yogyakarta, 2017)
Hospital XX is hospital a Type B hospital with a capacity of 189 beds. The hospital has implemented a remuneration system in 2010 until now. However, the benefits and objectives of the implementation of remuneration system has not been achieved because the employee satisfaction survey related to remuneration is only 42% while employee performance has not fulfilled management expectation. This can be seen in the results of the average achievement of individual performance is <70%. Google Terjemahan untuk Bisnis:Perangkat Penerjemah. The purpose of this study is to determine the effect of remuneration system development on employee satisfaction and performance. The type of research used is Action Research with participant method with population of all employees where the number of samples taken is 40 employees. Data analysis technique using descriptive analysis. The development of the remuneration system can improve employee satisfaction and performance, this can be seen in the results of observation on the implementation of the action of cycles II where there is an increase in employee satisfaction score of 3.4 and the performance-related score is 3.1. In this study proved that the development of remuneration system has a positive effect on employee satisfaction and employee performance.